If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(2x + -5) + -3(4x + -7) = 0 Reorder the terms: 9(-5 + 2x) + -3(4x + -7) = 0 (-5 * 9 + 2x * 9) + -3(4x + -7) = 0 (-45 + 18x) + -3(4x + -7) = 0 Reorder the terms: -45 + 18x + -3(-7 + 4x) = 0 -45 + 18x + (-7 * -3 + 4x * -3) = 0 -45 + 18x + (21 + -12x) = 0 Reorder the terms: -45 + 21 + 18x + -12x = 0 Combine like terms: -45 + 21 = -24 -24 + 18x + -12x = 0 Combine like terms: 18x + -12x = 6x -24 + 6x = 0 Solving -24 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 6x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 6x = 0 + 24 6x = 0 + 24 Combine like terms: 0 + 24 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 3(3-3x)+6(-2x-4)=-15 | | -4(3x-2)=16 | | -6(w+1)=1 | | 2x-5=3x-17 | | 10x-1+26x=95 | | -6[1-5v]=24 | | 15-3b=-5b+2b+18-3 | | -3n-8=-26 | | 15=h-17 | | 11-2(x)=-17 | | -6(w+6)=1 | | y=-4/3(1.3333)-8 | | 2x+1-5=7-1 | | 11-2x=-17 | | 4x+2=53 | | 7=8(1+2r)-5(1+3r) | | -3(4-3n)=-66 | | x+y+xy=120 | | 4/x+1/9= | | 5=5m-6 | | 2/5h-7=12/5h-2h+4 | | 5=5m+6 | | -63=5+4(1-3x) | | -6xy-2xz-9x+1=4y+4 | | x(2)+5x+6= | | 15-3b=5b+2b+18-3 | | -72=-9(m+12) | | -14=6x+34 | | (t+20)=(t-10)+t | | 3g-2g= | | 1x+10=6 | | 6x=12+3y |